Adapting benzoxazine chemistry for unconventional applications - Kiskan, Baris (Reactive & functional polymers, 2018)
Polybenzoxazines, as a kind of phenolics, are high performance thermosets with a range of features and overcoming some drawbacks of resole and novolac type phenolics. Most of the polybenzoxazines exhibit high Tg, high char yield, flame resistance, low water absorption, low shrinkage and also limited or no release of by-products during curing, they have good mechanical performance and are effective contender of high performance polymers such as bismaleimide resins. Thus, the interest in polybenzoxazines is continuously increasing in the polymer science as reflected by the number of scientific publications and patents. In this mini review, an overview about polybenzoxazines is reported highlighting the current advances and progress in the synthesis of benzoxazine based materials for unconventional uses that can be considered as smart applications ranging from self-healing materials to electrochromic devices. [Display omitted]